Bacterial microflora of the upper gastrointestinal tract in infants without diarrhoea - Challacombe, D. N. (1974)
The upper gastrointestinal microflora has been studied by intubation in a group of infants without diarrhoea. The aerobic flora of the nose and throat, and the aerobic and anaerobic flora of the stomach and duodenum have been defined. Prolonged duodenal intubation has been shown to increase the number of coliforms isolated and bacteriological findings after prolonged intubation should therefore be interpreted with care.